Reworking the Bond Girl Concept in the Craig Era. Issue 1 (2nd January 2018) - Funnell, Lisa
Abstract: This article explores how the Bond Girl concept is deconstructed across the orphan-origin trilogy— Casino Royale, Quantum of Solace, and Skyfall —to accommodate the rise of a new heroic model that focuses on strength and resilience. The qualities associated with the Bond Girl are distributed across at least two characters per film. This opens up space for outlier women—Vesper Lynd, Camille Montes, M—and adjustments to the gender politics of the franchise. The archetype is reintroduced in Spectre as Dr. Madeleine Swann can be read as a composite of previous Bond Girls. The film also reworks the narratives associated with the outlier women in the Craig era, bringing their qualities into the Bond Girl fold while reinstituting a phallocentric order in the franchise through the (re)positioning of Bond as a romantic hero.